2019
DOI: 10.12688/f1000research.17147.1
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping analysis of the Pax9 Gene in patients with maxillary canine impaction

Abstract: Background: Paired-box gene 9 (PAX9) mutation is potentially associated with impaction in some patient populations. Here, we analyzed the relationship between PAX9 polymorphism and the occurrence of maxillary canine impaction. Methods: Patients with and without maxillary canine impaction were selected based on specific inclusion criteria, and samples of genomic DNA were obtained from a buccal mucosa swab. DNA was amplified by polymerase chain reaction and sequenced for further bioinformatics analysis to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Additional mutations include c.146delC, c.218dupG, c.256_262dup, c.76C>T, and C.140G>C, among others (8). In the present study, we found rs12881240 (26,27) (exon 3, probands 1 and 5) and rs4904210 (27,28) (exon 3, probands 1.1 and 5) that have previously been reported to be associated with NSDA. In Mexican families, rs12881240 and rs4904210, both in exon 3, have been reported; they impact protein and messenger RNA (mRNA) structures (13).…”
Section: Discussionsupporting
confidence: 72%
“…Additional mutations include c.146delC, c.218dupG, c.256_262dup, c.76C>T, and C.140G>C, among others (8). In the present study, we found rs12881240 (26,27) (exon 3, probands 1 and 5) and rs4904210 (27,28) (exon 3, probands 1.1 and 5) that have previously been reported to be associated with NSDA. In Mexican families, rs12881240 and rs4904210, both in exon 3, have been reported; they impact protein and messenger RNA (mRNA) structures (13).…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, a thorough survey of the factors involved in their development is of major importance. Specific genetic factors have been reported to be responsible for the development of dental anomalies in each jaw [ 2 , 3 ]. In addition, disturbances created during tooth development may produce variations in the number of teeth (agenesis/supernumerary teeth) [ 4 ], their size and shape, and tooth bud position, which can affect both permanent and deciduous dentition of both jaws [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PDC seems to be an anomaly in development with genetic causes but precise etiology is not known up to date [ 60 – 63 ]. In the literature, Pax9 polymorphism is the most often mentioned as a responsible factor for palatal impaction of upper canines [ 64 71 ]. Devi et al [ 68 ], in particular, aimed to evaluate the association between PAX9 polymorphisms and palatally impacted canines.…”
Section: Discussionmentioning
confidence: 99%